A model describing the oxidation rate of lubricating greases - Schneidhofer, Christoph; Schandl, Michael; Dörr, Nicole; Lugt, Piet M. (Frontiers in Mechanical Engineering, 2025)
IntroductionGrease oxidation in rolling bearings causes a loss of grease in the track and hence a loss of lubricity in the bearing. This work addresses loss of grease via evaporation and oxidation due to thermal-oxidative stress applied to two lubricating greases.MethodsFor this purpose, the oxidation stability of two greases was determined using a modified micro-coking test over a wide temperature range from 100°C to 190°C. Grease analyses by means of antioxidant content, oxidation and weight loss were used to develop a lifetime model to describe the change in mass as a function of temperature, time, and grease type due to oxidation based on the Arrhenius equation.Results and discussionThe developed model describes the correlation between the findings from grease analyses and shows increased oxidation and evaporation after the induction period when antioxidants are almost consumed.